Trauma, space and embodiment: the sensorium of a divided city - Koureas, Gabriel (My University, 2008)
This paper investigates the ways in which the divided city of Nicosia (Cyprus), scarred by wars and ethnic conflicts that have left open wounds in the fabric of the city, tries to heal itself and incorporate its traumatic memories within its spatial organization, and asks if such an incorporation is possible. The visual and sensorial language of the city of Nicosia is examined in detail in relation to its ‘politography’, concentrating on issues of space, borders (both physical and psychic), memory and trauma. Their interactions with hegemonic and personal narratives are discussed in order to interrogate artistic intersections in the spatial and psychic parameters of the city. The paper aims to demonstrate that artistic production in the city of Nicosia is embedded in the space of the city. Like the space of the city, these works demand our participation, our interaction through all our senses. Encounters with these works, like encounters with the city, produce embodied experiences that are no longer framed as representations. In experiencing these works and the city, one is unable to rely solely on vision, as they call for our hearing, smell and tactility in comprehending spatially and artistically the impact of war and conflict. It is only by understanding the sensorial impact of trauma that one can begin to comprehend the political and social conditions in the city of Nicosia and its artistic production.
Keywords: Trauma; Memory; Reconciliation; Conflict; Senses; Affect; Cyprus